Church-Based Breast Cancer Screening Education: Impact of Two Approaches on Latinas Enrolled in Public and Private Health Insurance Plans - Angela Sauaia, MD, PhD; Sung-joon Min, PhD; David Lack; Cecilia Apodaca; Diego Osuna, MD; Angela Stowe; Gretchen F. McGinnis; Lisa M. Latts, MD, MSPH, MBA; Tim Byers, MD, MPH (Centers for Disease Control and Prevention, 2007)
Introduction The Tepeyac Project is a church-based health promotion project that was conducted from 1999 through 2005 to increase breast cancer screening rates among Latinas in Colorado. Previous reports evaluated the project among Medicare and Medicaid enrollees in the state. In this report, we evaluate the program among enrollees in the state's five major insurance plans.Methods We compared the Tepeyac Project's two interventions: the Printed Intervention and the Promotora Intervention. In the first, we mailed culturally tailored education packages to 209 Colorado Catholic churches for their use. In the second, promotoras (peer counselors) in four Catholic churches delivered breast-health education messages personally. We compared biennial mammogram claims from the five insurance plans in the analysis at baseline (1998-1999) and during follow-up (2000-2001) for Latinas who had received the interventions. We used generalized estimating equations (GEE) analysis to adjust rates for confounders.Results The mammogram rate for Latinas in the Printed Intervention remained the same from baseline to follow-up (58% [2979/5130] vs 58% [3338/5708]). In the Promotora Intervention, the rate was 59% (316/536) at baseline and 61% (359/590) at follow-up. Rates increased modestly over time and varied widely by insurance type. After adjusting for age, income, urban versus rural location, disability, and insurance type, we found that women exposed to the Promotora Intervention had a significantly higher increase in biennial mammograms than did women exposed to the Printed Intervention (GEE parameter estimate = .24 [±.11], P = .03).Conclusion For insured Latinas, personally delivering church-based education through peer counselors appears to be a better breast-health promotion method than mailing printed educational materials to churches.